Facile eco-friendly sol-gel synthesis of highly monodispersed Zn@silica nanospheres with dual antibacterial mechanism against multidrug-resistant bacteria - Yesul Jeong; Hyeran Kim; Soon Chang Lee; Ha-Rim An; Jong-Seong Bae; Yunju Choi; Byoungchul Son; Ji-In Park; Da-Hye Kim; Jiwon Seo; Eui-Jeong Han; Ji-Hyun Lee; et al. (Chemical Engineering Journal, 2026)

Dexamethasone nanocrystals-embedded hydroxypropyl methylcellulose hydrogel increases cochlear delivery and attenuates hearing loss following intratympanic injection - Min Young Jeong; Subin Kim; Hye Rim Kim; Jiae Jeon; Seong Su Won; Keum-Jin Yang; Jun Soo Park; In Gyu Yang; Dong Geon Lee; Jin Hyuk Myung; Yoon-Gyoon Kim; Sung Giu Jin; et al. (Carbohydrate Polymers, 2024)

Exploring the potential hypothalamic role in mediating cisplatin-induced negative energy balance - Yang Tae Kim; Byong Seo Park; Hye Rim Yang; Seon Yi; Il Seong Nam-Goong; Jae Geun Kim (Chemico-Biological Interactions, 2023)

Estimation of Genetic Parameters and Optimum Breeding Programme Design in Korean Flatfish Breeding Population - Phuong Thanh N. Dinh; Jong-Won Park; Waruni Ekanayake; Yeongkuk Kim; Dooho Lee; Dain Lee; Hyo Sun Jung; Julan Kim; Hye-Rim Yang; Heegun Lee; Sangwon Yoon; Jeong-Ho Lee; et al. (Fishes, 2022)
Olive flounder (Paralichthys olivaceus) is a vital aquaculture species in East Asia. However, few studies that estimate the genetic parameters of this species have been conducted. We estimated the genetic parameters of growth traits and designed an optimum breeding programme for this species. Heritability, genetic and phenotypic correlations, and breeding values were estimated for growth traits: body weight (BW), total length (TL), and condition factor (CF). A linear mixed animal model using the restricted maximum likelihood (REML) algorithm was applied to the statistical analysis of 9 traits (BW, TL, and CF at 11, 18, and 22 months of age) for a total of 54,159 animals from 7 generations. Increases of 13%, 8%, and 6.5% in BW, TL, and CF at the harvest stage were observed, respectively, after 7 generations of selection. The heritabilities of all growth traits were moderate, ranging from 0.35 to 0.46. The phenotypic and genetic correlations between BW and TL were high and positive in all three stages (0.91 and 0.92, 0.91 and 0.93, and 0.88 and 0.91). The estimated breeding values of BW and TL increased over the generations; however, the estimated breeding value of CF fluctuated. The optimum progeny number within full-sib families for an accuracy of 0.632 is suggested to be between 10 and 25. Findings indicated that a considerable response to selection and single-trait selection based on BW would be effective in olive flounder.

Detection of 94 compounds related to sexual enhancement including sildenafil, tadalafil, vardenafil and their analogues in various formulations of dietary supplements and food samples using HPLC and LC-MS/MS - Ji Hyun Lee; A. Young Min; Ok Rim Park; Ji Hye Han; Yoon Ji Yang; Hyungil Kim; Sun Young Baek (Food Additives & Contaminants: Part A, 2021)

Analysis of miRNA expression profiling in melatonin-exposured endothelial cells - Gun Woo Son; Hana Yang; Hye Rim Park; Seung Eun Lee; Young-Ho Jin; Cheung-Seog Park; Yong Seek Park (Molecular & Cellular Toxicology, 2016)

Crotonaldehyde-exposed macrophages induce heme oxygenase-1 expression as an adaptive mechanism - Seung Eun Lee; Hana Yang; Gun Woo Son; Hye Rim Park; Young-Ho Jin; Cheung-Seog Park; Yong Seek Park (Molecular & Cellular Toxicology, 2015)

Microarray analysis of gene expression in 3-methylcholanthrene-treated human endothelial cells - Hye Rim Park; Hana Yang; Gun-Dong Kim; Gun Woo Son; Yong Seek Park (Molecular & Cellular Toxicology, 2014)